PERILAKU OVERPROTECTIVE ORANG TUA DENGAN KEPERCAYAAN DIRI PADA MAHASISWA DI UNIVERSITAS KRISTEN SATYA WACANA - Maharani Sekar Asih, Patricia; Hari Soetjiningsih, Christiana (CV. Lafadz Jaya, 2023)
This study aims to prove the relationship between parental overprotective behavior and self-confidence in college students. The participants of this study amounted to 105 people with data collection methods using accidental sampling techniques. The scale used is a self-confidence scale compiled by Lauster and an overprotective behavior scale compiled by Wattimena which was modified by Huwae which has been validated constructively. overprotective can have an impact on self-confidence in children. The data analysis technique used is Pearson's product moment correlation technique. From the results of data analysis, the correlation coefficient (r) was -0.191 with a significance value of 0.025 (p<0.05) which means that there is a significant negative relationship between overprotective behavior and self-confidence. This shows that the higher the overprotective behavior of parents, the lower the self-confidence, otherwise the lower the overprotective behavior of parents, the higher the self-confidence.